2005
DOI: 10.1046/j.1540-8167.2005.40592.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Impedance Monitoring and Patient Alert Feature in Implantable Cardioverter Defibrillators:

Abstract: Recent advances in implantable cardioverter defibrillator (ICD) technology have enabled implementation of an automatic monitoring feature in ICDs that provides daily measurements of several technical parameters such as battery status, pacing, and high-voltage impedance. The system alerts the patient with an audible alarm to contact the physician in case the measured parameters are not within normal limits. Early detection of intermittent and potentially serious complications justifies routine use of this featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Becker et al reported that standard impedance‐measurement‐based patient alerts in ICDs are useful additional tools for early detection of lead failure 12 . However, these impedance measurements alone seemed to be insufficient for inappropriate therapy prevention 13,14 . Accordingly, the research focus shifted to the combined use of impedance measurements with quantitative measures of oversensing resulting in a better and earlier lead failure detection 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Becker et al reported that standard impedance‐measurement‐based patient alerts in ICDs are useful additional tools for early detection of lead failure 12 . However, these impedance measurements alone seemed to be insufficient for inappropriate therapy prevention 13,14 . Accordingly, the research focus shifted to the combined use of impedance measurements with quantitative measures of oversensing resulting in a better and earlier lead failure detection 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…One failure was signaled by an impedance change and the other by noise on the shocking coil in the presence of a normal shocking impedance. Although failure of high-voltage conductor impedance monitoring has been reported, 14 additional studies are needed to determine whether impedance monitoring or electrogram analysis can prevent adverse events caused by high-voltage conductor failure.…”
Section: Discussionmentioning
confidence: 99%
“…No inappropriate therapy was delivered until the day of admission, although recurrent episodes of nonsustained ventricular fibrillation were detected a few days before the fatal event. Alarm systems in the defibrillators may help to detect lead malfunction early 13,14 . In the present case, the defibrillator implanted was equipped with a patient alert system, which alarms if the impedances of the pace/sense lead or the high‐voltage lead exceed predefined ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Alarm systems in the defibrillators may help to detect lead malfunction early. 13,14 In the present case, the defibrillator implanted was equipped with a patient alert system, which alarms if the impedances of the pace/sense lead or the high-voltage lead exceed predefined ranges. The patient alert was activated, but did not alarm because values for impedances were within the normal range, although the lead was dislodged.…”
Section: Discussionmentioning
confidence: 99%